62. The Return of Educational Radio? - Berman, Sally D. (International Review of Research in Open and Distributed Learning, 2008)
This paper examines one of the traditional technologies of distance education, radio, and presents examples of educational and community radio usage in Asia and Africa. Instead of merely transposing western approaches to distance education in developing countries, it is suggested that the developed world can learn from uses of radio in developing countries, and that the medium deserves greater attention as a means of giving educational opportunity to rural, isolated peoples worldwide.